2010
DOI: 10.1074/jbc.m109.077271
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous NAD Blocks Cardiac Hypertrophic Response via Activation of the SIRT3-LKB1-AMP-activated Kinase Pathway

Abstract: Since the discovery of NAD-dependent deacetylases, sirtuins, it has been recognized that maintaining intracellular levels of NAD is crucial for the management of stress response of cells. Here we show that agonist-induced cardiac hypertrophy is associated with loss of intracellular levels of NAD, but not exerciseinduced physiologic hypertrophy. Exogenous addition of NAD was capable of maintaining intracellular levels of NAD and blocking the agonist-induced cardiac hypertrophic response in vitro as well as in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
350
4
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(380 citation statements)
references
References 52 publications
(65 reference statements)
19
350
4
7
Order By: Relevance
“…Treatment with exogenous NAD blocked the induction of atrial natriuretic factor release from nuclei, thus suggesting the antihypertrophic activity of NAD [6]. The results indicated that phenylephrine (PE, 20 µM)-mediated activation of these promoters was significantly reduced by treatment of cells with NAD, thus again demonstrating the anti-hypertrophic potential of NAD [6,19,20]. Early, Sukoyan has shown that treatment with oxidized form of NAD (preparation of Nadcin  ) reversed ischemic-reperfusion injury of myocardium in experimental models [16][17][18] and Bokeria confirm these results in randomized controlled study in patients with unstable angina pectoris and bypass grafting [21].…”
Section: Discussionsupporting
confidence: 58%
“…Treatment with exogenous NAD blocked the induction of atrial natriuretic factor release from nuclei, thus suggesting the antihypertrophic activity of NAD [6]. The results indicated that phenylephrine (PE, 20 µM)-mediated activation of these promoters was significantly reduced by treatment of cells with NAD, thus again demonstrating the anti-hypertrophic potential of NAD [6,19,20]. Early, Sukoyan has shown that treatment with oxidized form of NAD (preparation of Nadcin  ) reversed ischemic-reperfusion injury of myocardium in experimental models [16][17][18] and Bokeria confirm these results in randomized controlled study in patients with unstable angina pectoris and bypass grafting [21].…”
Section: Discussionsupporting
confidence: 58%
“…Recent evidence has shown that SIRT3 is involved in mitochondrial energy metabolism and biogenesis (56) and preservation of ATP biosynthetic capacity in the heart (45). SIRT3 knock-out resulted in a marked decrease in basal ATP in vivo (57) and eliminated the role of SIRT3 in protection of cells from oxidative stress (58). Our study suggests that viniferin increases SIRT3, stimulates AMPK activities, and preserves NAD levels, and therefore, could have a pivotal role in protecting neurons from mutant Htt, which promotes bioenergetic failure.…”
Section: Discussionmentioning
confidence: 82%
“…Sirt3-deficient mice develop cardiac hypertrophy, whereas transgenic animals overexpressing SIRT3 in the heart are protected against agonist-mediated cardiac hypertrophy (84). At the molecular level, SIRT3 deacetylates and activates LKB1, thereby activating AMP-activated kinase, which suppresses Akt phosphorylation (85). Moreover, SIRT3-dependent deacetylation of FoxO3a leads to its nuclear localization and enhanced expression of antioxidant genes, such as manganese superoxide dismutase, reducing cellular ROS levels (84).…”
Section: Cardiovascular Diseasementioning
confidence: 99%